Penyisihan Nitrogen dengan Proses Anammox Menggunakan Lumpur Muara Penjalinan Kota Padang sebagai Inokulum: Nitrogen Removal by Anammox Process Using Sludge from Muara Penjalinan of Padang City as Inoculum - Faldi Lulrahman; Shinta Silvia; Zulkarnaini Zulkarnaini (Jurnal Teknologi Lingkungan, 2022)
The purpose of this study was to analyze nitrogen removal by anaerobic ammonium oxidation (anammox) process using sludge from Muara Penjalinan Padang as an inoculum in a filter bioreactor (FtBR). The configuration of FtBR consisted of a housing filter with an effective volume of 1,500 mL and a string wound filter cartridge of 0.5 µm as a carrier for the growth of anammox bacteria. The artificial wastewater was made using seawater containing ammonium and nitrite with a concentration of 70 mg-N/L, which was delivered to the reactor continuously with a hydraulic retention time (HRT) of 24 hours. Influent and effluent samples were collected once-twice a week to analyze the concentration of ammonium, nitrite, and nitrate, based on Nessler, spectrophotometry, and UV screening methods. Process anammox takes place in FtBR based on the average ratio of ?NO2--N/?NH4+-N and ?NO3--N / ?NH4+-N of 0.986 dan 0.239. The nitrogen removal performance was calculated based on the ammonium conversion efficiency (ACE), nitrogen removal efficiency (NRE), nitrogen loading rate (NLR), and nitrogen removal rate (NRR). After operating the reactor for 143 days, the nitrogen removal of ACE, NRE, and NRR were 20.268%, 16. 872%, and 0.026 kg-N/m3·d at NLR 0.1804 kg-N/m3·d. Keywords: Anammox, Filter bioreactor, Muara Penjalinan, Seawater, Sludge ABSTRAK Anaerobic ammonium oxidation (anammox) merupakan penyisihan amonium menjadi gas nitrogen menggunakan nitrit sebagai penerima elektron dan berkontribusi dalam penyisihan nitrogen di lautan. Penelitian ini bertujuan untuk menganalisis penyisihan nitrogen melalui proses anammox menggunakan lumpur Muara Penjalinan Kota Padang sebagai inokulum pada filter bioreactor (FtBR). Konfigurasi FtBR terdiri atas housing filter dan string wound filter cartridge sebagai media lekat untuk pertumbuhan biomassa anammox yang dioperasikan secara kontinu dengan hydraulic retention time (HRT) 24 jam pada suhu ambien. Limbah artifisial dibuat menggunakan air laut yang dengan menambahkan 70 mg-N/L amonium dan nitrit masing-masingnya yang dipompakan ke reaktor secara kontinu. Pengambilan sampel influen dan efluen dilakukan satu hingga dua kali dalam seminggu untuk pengukuran konsentrasi amonium, nitrit dan nitrat berdasarkan metode Nessler, spektrofotometri, dan skrining spektrofotometri ultraviolet. Proses anammox berlangsung dalam reaktor berdasarkan rasio ?NO2--N/?NH4+-N dan ?NO3--N / ?NH4+-N sebesar 0,986 dan 0,239 yang mendekati stoikiometri reaksi anammox. Setelah operasional reaktor selama 143 hari didapatkan kinerja penyisihan nitrogen maksimal ammonium conversion efficiency (ACE), nitrogen removal efficiency (NRE) dan nitrogen removal rate (NRR) berturut-turut 20,268%, 16,872% dan 0,026 kg-N/m3.h pada nitrogen loading rate (NLR) 0,1804 kg-N/m3.h. Kata kunci: Anammox, Filter bioreactor, Muara Penjalinan, Air laut, Lumpur